Makna Teologis Dangding Kinanti Ngahurun Balung Karya Haji Hasan Mustapa: Analisis Hermeneutika Paul Ricoeur - Ilham Maulana (Jurnal Penelitian Ilmu Ushuluddin, 2021)
The purpose of this study was to analyze the theological meaning of Dangding Kinanti Ngahurun Balung by using Paul Ricoeur's hermeneutical analysis. The method used is a type of qualitative research with literature study. The results and discussion of this research include the biography of Haji Hasan Mustapa, the text of Dangding Kinanti Ngahurun Balung and analysis of the theological meaning of Dangding Kinanti Ngahurun Balung. The conclusion of this study is that the theological meaning of Dangding Kinanti Ngahurun Balung is aware of the limitations in the quest to know God, so that humans are required to be humble before God and surrender to Him as a servant. This research is recommended for further studies on Haji Hasan Mustapa's dangding texts and the use of hermeneutics as an analytical tool, especially Paul Ricoeur's hermeneutics and studies on theology.